THE IMPACT OF MANDATORY AND VOLUNTARY DISCLOSURE OF HARD AND SOFT INFORMATION ON FINANCIAL STATEMENT USERS IN IRAQ (The Journal of Modern Project Management, 2025)
It examined both mandatory and voluntary disclosure’s effect on users of financial statements and paid a special consideration to distinguishing soft information from hard information. It was grounded in a literature review that highlighted disclosure quality as a key drivers in enhancing market efficiency and supporting investors’ decision-making process. Empirical evidence was gathered on a sample size involving 20 non-financial firms listed on the Iraq Stock Exchange. The findings highlighted disclosure practices regarding both return on equity and return on assets. Specifically, firms that utilized vague or speculative forward-looking narratives exhibited a negative association with performance while disclosures that featured a positive orientation and firm value clarity exhibited a positive relationship with improved market performance. Additionally, objectivity and quantifiability of hard information was positively associated with firm performance. The research further exhibited that poorly performing firms highly relied upon vague and narrative disclosures whilst better-performing firms utilized full reporting verifiable and factual. Generally, research contributes to existing literature to the extent that quality of disclosure has a significant association with financial performance both within both mandatory and voluntary reporting paradigms and such association persisted especially where emerging markets were concerned.